Islamic Philanthropy as Monetary Circulation Channels: Theory Development and Panel VAR Evidence from OIC Countries - Syamsul Bachri Soamole (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
This study develops a Circulatory Philanthropy Theory, a theoretical extension of Islamic monetary thought positioning Islamic philanthropy (sadaqah, zakat, waqf) as complementary non-commercial channels of wealth circulation within riba-free monetary frameworks. Using sequential mixed-methods, document-based grounded analysis of classical Islamic scholarship to construct theory, followed by panel VAR econometrics for 10 OIC countries (2012–2022, N=110), the framework conceptualizes philanthropic instruments as differentiated temporal mechanisms: sadaqah as a short-run catalyst, zakat as a medium-run stabilizer, and waqf as a long-run productive anchor. Impulse Response Function (IRF) analysis reveals immediate positive GDP responses to philanthropic shocks (Sadaqah: 0.27 percentage points, Zakat: 0.19, Waqf: 0.27 at period 0), followed by mean-reverting dynamics consistent with temporary demand-side effects. Forecast Error Variance Decomposition (FEVD) shows that waqf explains 40.2% of GDP variance at period 2, exhibiting a U-shaped pattern (95% → 1.9% → 40.2%) that supports its dual character as both immediate activator and sustained structural determinant, outperforming transitory transfers (sadaqah/zakat: <2% by period 2). Negative velocity responses suggest institutional intermediation lags and precautionary saving among recipients. Panel Granger causality indicates income-driven endogeneity (GDP → Sadaqah, p=0.050), implying circulation effectiveness depends on institutional capacity. Findings provide qualified empirical support that Islamic philanthropic instruments can exert meaningful macroeconomic influence when institutionally supported, though effectiveness remains conditional on country-specific governance and digital disbursement infrastructure. The study contributes a novel theoretical framework and preliminary panel evidence that philanthropic flows are analytically tractable as macro-level circulation and stabilization mechanisms.